2014
DOI: 10.1155/2014/531074
|View full text |Cite
|
Sign up to set email alerts
|

Malaria, Typhoid Fever, and Their Coinfection among Febrile Patients at a Rural Health Center in Northwest Ethiopia: A Cross-Sectional Study

Abstract: Background. Malaria and typhoid fever are major public health problems in tropical and subtropical countries. People in endemic areas are at risk of contracting both infections concurrently. Objectives. The study was aimed at determining the prevalence and associated risk factors of malaria, typhoid, and their coinfection among febrile patients. Methods. A cross-sectional study was conducted on 200 febrile patients suspected for malaria and/or typhoid fever from April to May, 2013, at Ayinba Health Center, Nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
66
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(96 citation statements)
references
References 12 publications
13
66
17
Order By: Relevance
“…However, the sero-prevalence of Rickettsia infection in this study was lower than the one reported from other parts of Ethiopia [ 19 , 28 ], but higher than the findings of the studies by Tadesse and Tadesse [ 18 ] and Birhane et al [ 29 ]. The variation might be linked to the type of environment in the study area.…”
Section: Discussioncontrasting
confidence: 90%
“…However, the sero-prevalence of Rickettsia infection in this study was lower than the one reported from other parts of Ethiopia [ 19 , 28 ], but higher than the findings of the studies by Tadesse and Tadesse [ 18 ] and Birhane et al [ 29 ]. The variation might be linked to the type of environment in the study area.…”
Section: Discussioncontrasting
confidence: 90%
“…Any association was not found between male and female concerning "typhomalaria (p = 0.46). However, the "typhomalaria" prevalence was higher in women, according with one study in Ethiopia [11]. Thus, The major limitation of this study was the use of SDWF only for the TF diagnosis.…”
Section: Discussionmentioning
confidence: 74%
“…In Ethiopia, 6.5% of prevalence was reported [11] and 5% to 40% in Nigeria [10,12,13]. In Burkina Faso, to our best knowledge, no data on "typhomalaria" was published.…”
Section: Introductionmentioning
confidence: 99%
“…A study from Ethiopia reported coinfection rate of 6.5% using Widal test and 0.5% with blood culture, which is in accordance to our study. 9 However, in a recent report from Nigeria, a co-infection rate of 28% was reported using the same set of tests for typhoid and malaria which could be attributed to higher endemicity of malaria in this region. 10 These findings suggest that the diagnosis of typhoid fever presents a greater diagnostic dilemma in comparison to malaria.…”
Section: Discussionmentioning
confidence: 89%